2017
DOI: 10.5301/hipint.5000573
|View full text |Cite
|
Sign up to set email alerts
|

Soft tissue reinforcement with a Leeds-Keio artificial ligament in revision surgery for dislocated total hip arthroplasty

Abstract: soft tissue around hip joint have an important relation to the stability of THA, its repair to prevent dislocation is recommended not only after revision THA (19-22) as well as after primary THA (23-28). Patients with joint laxity or soft tissue defects are particularly prone to failure to recover despite treatment for dislocated THA (19, 23). We have been carrying out soft tissue reinforcement with the Leeds-Keio (LK) artificial ligament to treat intractable dislocation after THA in cases in which soft tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
3
0
2
Order By: Relevance
“…On the other hand, in Group 2, the artificial ligament significantly impacted on the mechanics of reconstruction, giving 64% and 17% survival rates, at 120 months. The mechanical role of artificial ligaments in improving mechanics of the reconstruction is well known [ 6 , 32 , 33 ]. However, due to lower soft tissue excision, a limited resection probably has lower impact on hip stability.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in Group 2, the artificial ligament significantly impacted on the mechanics of reconstruction, giving 64% and 17% survival rates, at 120 months. The mechanical role of artificial ligaments in improving mechanics of the reconstruction is well known [ 6 , 32 , 33 ]. However, due to lower soft tissue excision, a limited resection probably has lower impact on hip stability.…”
Section: Discussionmentioning
confidence: 99%
“…При ревизионном эндопротезировании усиленное ушивание тоже показывает эффективность: после ревизионного эндопротезирования задним доступом ре-ревизия по поводу вывихов делалась в 1,9% [93] и в 2,5% [94] случаев в группах усиленного ушивания и в 10% случаев в группах обычного ушивания [93,94]. Недавно S. Aota c соавторами предложили новую методику усиленного ушивания с использованием синтетической связки Leeds-Keio, которая, по их данным, позволила стабилизировать сустав в 82% случаев ревизий по поводу сложных случаев многократных вывихов [95]. В 1987 г. S.J.…”
Section: таблица 1 влияние офсета на вывихunclassified
“…При ревизии, конечно же, важны и имеют место уже описанные маневры по усиленному ушиванию при задних доступах [93,94], пластика синтетическими материалами [95], дистализация большого вертела [96]. Теоретически в некоторых редких случаях есть перспектива у артроскопической реконструкции капсулы [97].…”
Section: классификация хирургической тактикиunclassified
“…Sufficient soft-tissue tension that is formed by the joint capsule, short external rotators, and gluteal muscles also is important in reducing dislocation rates following revision total hip arthroplasty 42 . Multiple studies have demonstrated reduced rates of dislocation with the addition of posterior soft-tissue repair in revision total hip arthroplasties 61 . Following revision total hip arthroplasties, 1.9% of hips that were revised through the posterior approach with soft-tissue repair dislocated compared with 10% of revised hips without soft-tissue repair 62 .…”
Section: Soft-tissue Tension and Repairmentioning
confidence: 99%
“…Following revision total hip arthroplasties, 1.9% of hips that were revised through the posterior approach with soft-tissue repair dislocated compared with 10% of revised hips without soft-tissue repair 62 . Aota et al detailed a novel soft-tissue reinforcement technique with a Leeds-Keio ligament during revision surgery, resulting in 82% of cases being resolved of their intractable dislocation 61 . Moreover, Dargel et al reported that softtissue tension can be increased without extending the leg by increasing the offset between the femoral stem and the rotation center of the hip joint 3 .…”
Section: Soft-tissue Tension and Repairmentioning
confidence: 99%